Literature/Ethics/Reading. Issue 3 (December 2017) - Nayar, Pramod K.
Abstract : The chapters on ethics and / of reading in Ranjan Ghosh and J. Hillis Miller's Thinking Literature across Continents propose two models of responding to literature. Ghosh sees literature as embodying a hunger for Otherness. Miller insists on the ethical authority of a given literary work over the reader, its ethical obligations to the characters within and to the readers it addresses, and the ethical acts and decisions of the characters within the work. Ghosh's account of literature as hunger opens up aesthetics to the question of the ethical, including the ethics of representation, reading, and Othering. Along with Miller's formula for reading ethically, the two chapters offer us an approach that may be termed, after Kwame Anthony Appiah, cosmopolitan reading, made possible by the sympathetic imagination that literature embodies.